Cara Kromatografi Preparatif : Penggunaan pada isolasi senyawa alam / K. Hostettmann, m. Hostettmann, A. Marston ; penerjemah, Kosasih Padmawinata ; penyunting, Titet Sutomo - HOSTETTMANN, K; Hostettman, M; Marston, A; Padmawinata, Kosasih; Sutomo, Tetet (Penerbit ITB, 1995)
9 a, 188 hlm : ilus. ; 21 cm